Agile transformation - Little, Jason; Safari eBooks ([S.l.] : Addison-Wesley Professional, 2012)
"Implementing Agile is a huge organizational change, and it's difficult. Today's organizations are complex adaptive systems that will react in unpredictable ways when change is introduced. Some consider Agile as processes and tools while others consider Agile as a mindset. Organizations are far too complex to assume one path to agility is the right path for everyone. Jason Little has been in the software industry since 1996 and has been helping organizations adopt Agile practices since 2007 as a Scrum Master, Product Owner and Coach. In this video Jason will show you a 4 step model that will help you shape your path to business agility. In addition, this video talks about how to leverage the Lean Startup method even if your organization is not a startup."--Resource description page.
Title from title screen.
Presenter, Jason Little.
Keywords: Organizational change; Organizational effectiveness; Agile software development; Electronic books